Rotura hepática en síndrome de HELLP: electrofulguración y uso de malla. Reporte de caso - Ramírez Cabrera, Juan Orestes (2019)
Hepatic subcapsular hematoma is a rare and lethal complication of HELLP syndrome presenting during pregnancy or the postpartum in women with severe preeclampsia or eclampsia. Maternal and perinatal mortality is high, hence the importance of prevention, early recognition, and timely and multidisciplinary treatment. We present a case of spontaneous rupture of subcapsular hepatic hematoma in which treatment consisted in electrofulguration and placement of hemostatic mesh, and a review of the literature.